Measurement of loss components in two induction machines and three types of frequency converters - Åström, Johan (My University, 2004)
This report presents the results obtained from measurements on two induction machines (IMs) fed by three different types of frequency converters; the focus has been on determining the different loss components of the drive system and how these varies with the frequency at different operating points. The mechanical power output was measured with a torque transducer and for determining the electric power a six-channel power analyzer was used. The main conclusion is that the method used gave good results; it managed to explain nearly all the losses in the induction machine. The part of the losses not accounted for was 13% in the worst case, which can represet the stray losses. Furthermore, it was established how the different loss components varied with frequency and load; it was found that the overall losses decreased with increasing frequency for all load situations An investigation of three field measurement methods was also preformed; the slip method, the current method and the air gap torque method were considered. The two first methods gave unsatisfying result. The air gap torque method gave a result very close to the measured output power. The estimated efficiency of the two methods varied with a maximum of 3.7% and this variation became less than 0.5% at loads above 0.5 p.u output power.
Keywords: Elkraftteknik; Electric power engineering